Herbal use and cultural influences in midwifery-led care: A scoping review - Aprianti, Nurul Azmi; Nurfitriyani, Ela; Kusteja, Nadya Fauzia; Adnani, Qorinah Estiningtyas Sakilah (Institute of Computer Science (IOCS), 2024)
This study explores the influence of herbal use and culture in midwifery-led care (MLC). The use of herbal medicine in the context of MLC is often influenced by cultural factors, making it crucial to understand the interaction between traditional and modern practices in maternal care. This research employs a scoping review method to examine articles from 2020 to 2024 that discuss the use of herbal medicine in the context of MLC. Data were gathered from various academic databases using keywords related to herbal use, culture, and MLC. Findings indicate that cultural factors significantly influence the preference for herbal medicine among pregnant women, especially in developing countries such as Indonesia, Ethiopia, and Malawi. Additionally, midwives' training on herbal use is crucial to ensure the safety and effectiveness of care. Many midwives show a strong interest in further learning about herbal use, but the lack of clear national guidelines and formal training hinders effective implementation. This study highlights the need for clear national guidelines and collaboration between traditional and modern healthcare providers to enhance the quality of maternal care. Comprehensive training for midwives on herbal use is essential to ensure safe and effective practices in MLC.